1998
DOI: 10.1093/emboj/17.24.7373
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic silencing of human rRNA synthesis: inactivation of the promoter selectivity factor SL1 by cdc2/cyclin B-mediated phosphorylation

Abstract: We have used a reconstituted cell-free transcription system to investigate the molecular basis of mitotic repression of RNA polymerase I (pol I) transcription. We demonstrate that SL1, the TBP-containing promoter-binding factor, is inactivated by cdc2/cyclin B-directed phosphorylation, and reactivated by dephosphorylation. Transcriptional inactivation in vitro is accompanied by phosphorylation of two subunits, e.g. TBP and hTAF I 110. To distinguish whether transcriptional repression is due to phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
130
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(131 citation statements)
references
References 52 publications
0
130
0
1
Order By: Relevance
“…Previous studies revealed that the shutdown of rRNA synthesis during mitosis and early G 1 phase is due to inactivation of TIF-IB/SL1 and UBF (Heix et al, 1998;Klein and Grummt, 1999). Growth-dependent regulation of Pol I, on the other hand, has been attributed to alterations in the amount or activity of TIF-IA (Buttgereit et al, 1985;Schnapp et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that the shutdown of rRNA synthesis during mitosis and early G 1 phase is due to inactivation of TIF-IB/SL1 and UBF (Heix et al, 1998;Klein and Grummt, 1999). Growth-dependent regulation of Pol I, on the other hand, has been attributed to alterations in the amount or activity of TIF-IA (Buttgereit et al, 1985;Schnapp et al, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…In prophase, these nucleoli disassemble and their transcription becomes repressed to allow the stripped rDNA to segregate with the rest of the genome. Nucleolar transcription is downregulated by the CDK1-cyclin B kinase, whose phosphorylation of promoter selectivity factor SL1 prevents the formation of the PolI pre-initiation complex [63][64][65] . Similar to yeast Rio1, RIOK1 might just as well contribute to the transcriptional repression of PolI.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription termination factor 1 (TTF-1) and SL-1 are phosphorylated by cdk2/Cyclin B at the G 2 /M transition. 2,48 The phosphorylation of SL-1 prevents its association with UBF which inhibits rRNA transcription, despite the fact that all factors remain associated with the chromatin. 49 UBF is also phosphorylated and inactivated in mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this process must be tightly regulated to ensure that the proper levels of transcription are congruent with the cellular requirements for protein production. The rate of rRNA transcription and elongation can be modulated by several factors, including growth factors, 1 cell cycle, 2 and cellular stress. 3 RNA polymerase I (Pol I) is the polymerase dedicated to transcribing the 47S pre-rRNA transcript.…”
mentioning
confidence: 99%
See 1 more Smart Citation